2006
DOI: 10.1016/j.ijdevneu.2005.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Early callosal absence disrupts the establishment of normal neocortical structure in Swiss mice

Abstract: In the present study, we tested the hypothesis that the ontogenetic development of the corpus callosum is relevant for the establishment of a normal neocortical structure. To that effect, neocortical morphology (thickness and neuronal density) was analyzed in adult Swiss mice rendered acallosal by midline transection at the first postnatal day (Acallosal group) and in non-manipulated mice. The neocortical thicknesses and neuronal densities of layers II+III through VI were measured in area 6 and at the 17/18a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 82 publications
(123 reference statements)
1
6
0
1
Order By: Relevance
“…As the majority of axons crossing the CC arise from neurons within the neocortex (Jacobson & Trojanowski, 1974;Ivy & Killackey, 1981;Ribeiro-Carvalho et al, 2006), we expected a close relationship between the quantity of neocortical neurons and the number of myelinated callosal fibers; a lack of correlation has not previously been described. Nevertheless, we were unable to retrieve a correlation in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…As the majority of axons crossing the CC arise from neurons within the neocortex (Jacobson & Trojanowski, 1974;Ivy & Killackey, 1981;Ribeiro-Carvalho et al, 2006), we expected a close relationship between the quantity of neocortical neurons and the number of myelinated callosal fibers; a lack of correlation has not previously been described. Nevertheless, we were unable to retrieve a correlation in the present study.…”
Section: Discussionmentioning
confidence: 84%
“…For each brain, five random disector pairs were counted for the GrDG, four pairs were counted for the Mol, CA1 and CA3 while two pairs were counted for the CA2. Neurons were distinguished from glial cells because the former have nuclei with distinct nucleoli and a large mean nuclear diameter with a fair amount of chromatin, whereas glial cells have smaller nuclei with little chromatin on a clear background (Abreu‐Villaça et al, 2002; Ribeiro‐Carvalho et al, 2006). In each section, a grid composed of 15 μm × 15 μm squares was positioned over each hippocampal region (magnification, 1000‐fold) and neurons and glial cells were counted within the frames.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it was reported that this lesion induces the formation of ectopic commisural fibers crossing to the contralateral hemisphere through callosal remnants above the septum, or the anterior commisure in hamsters (Lent, 1983). The same lesion in newborn mice is associated with reduced thickness of callosally innervated cortical areas (Ribeiro‐Carvalho et al, 2006), increased lateralization of rotations to the dominant side in free swimming tests (Manhaes et al, 2007), and a left side bias in paw preference tests (Manhaes et al, 2003). We previously found that callosotomy induces spontaneous alternation deficits in adult rats, which were not confounded by spatial preference biases (Miu et al, 2006).…”
Section: Methodsmentioning
confidence: 99%